“YOU HAVE BEEN WARNED”: SOUTH AFRICA'S GROWING RACISM IN THE EARLY APARTHEID ERA (Contemporary Journal of Social Science Review, 2025)
The present study conducts a stylistic analysis of Nadine Gordimer’s “Once Upon a Time” from a racial perspective, focusing on racism to address both the past and present conditions of apartheid in South Africa. The research aims to remove the ambiguity surrounding race to offer solutions to ongoing social issues. This study employs a qualitative descriptive approach to analyze the text and its meanings from a racial perspective, which proves beneficial for students in developing critical insights into the phenomenon of apartheid. By drawing on concepts of racism, stylistic analysis was used to understand the social inequalities in South Africa by identifying similes, imagery, irony, and lexical items like nouns, adjectives, and verbs within the text. The findings suggest that the intersection of racial politics and the segregation of white privilege contributes to violence in South Africa. This analysis highlights how language constructs and reinforces power dynamics, offering insights into the enduring effects of racial oppression in South African society.